Bilateral Moorens Ulcer - Anuj Sharma, Ravinder K. Gupta, Tarun Sood, Mandeep Tomar (Pakistan Journal of Ophthalmology, 2018)
A 36 year old male presented with chief complaints of foreign body sensation watering, redness, diminished vision ocular pain and photophobia in both eyes for last 2 months, On examination right eye revealed a perforated Mooren ulcer with uveal tissue herniation at 4 – 5 o’clock position. In both eyes, an undermined overhanging edge with grey white opacification and extending centrally and circumferentially could be appreciated. The pupil revealed peaking nasally OD due to impending uveal tissue herniation. No hypopyon or AC cells could be discovered on examination, Finally a diagnosis of Bilateral Mooren’s ulcer was arrived at and systemic immunosuppressive therapy was started in terms of oral methotrexate 10 mg once a week and oral prednisone 1 mg / kg / day, Bandage Contact Lens was applied in right eye and conjunctival recession was performed. Key Words: bilateral ulcus rodens corneae, peripheral ulcerative keratitis